Degradation Mechanism of Phenethylamine‐Based Interlayers in Perovskite Solar Cells and Breakthrough. Issue 7 (26th January 2023) - Lee, Seri; Kim, Gyu Min; Miyasaka, Tsutomu; Oh, Se Young
Abstract : Phenethylamine (PEA) halides (X) coated on perovskite (PVK) films are widely known as passivating layers, resulting in high performance in perovskite solar cells (PSCs). However, critical stability issues associated with phenethylamine halides (PEAX) in PSCs are observed, especially with Spiro‐OMeTAD, which prevented its practical use. Here, the mechanism by which PEAX negatively affects PSCs is reported. In addition, a method is devised to overcome the stability issue by employing poly(methyl methacrylate) (PMMA) at the PVK/PEABr interface to form dual PMMA/PEABr interlayers. Contrary to the general use of PEABr, the indirect contact of PEABr with PVK films by PMMA resulted in superior power conversion efficiencies (PCEs) and enhanced stability resulting from the retention of dipole moments even under aging. Further, effective methods of maximizing and retaining the dipole effect by heating PMMA/PEAX, as opposed to PSCs incorporating PEAX without PMMA being negatively affected by heat are exploited. The resulting PSCs with PMMA/heated PEABr exhibit a PCE of 21.63%, and retain 95% of their original performance a month after fabrication. Abstract : This study suggests that the general use of phenethylamine‐based interlayers results in the degradation of perovskite. Focusing on these degradation mechanisms, poly(methyl methacrylate) (PMMA) is a breakthrough in preventing direct contact between perovskite (PVK) and phenethylamine halides (PEAX). The PMMA/PEAX double interlayer is effective for both stability and efficiency of the perovskite solar cell, and heat treatment (PMMA/H‐PEABr) maximizes overall performance.